American Imperialism and the Japanese Encounter with "Religion": 1853-1858 - Horii, Mitsutoshi (Studi e materiali di storia delle religioni, 2016)
It was during the years of intense American-Japanese treaty negotiations from 1853 when the Japanese first encountered the generic concept 'religion'. The generic meaning of 'religion' was initially lost in the linguistically multi-layered process of translations during the earliest stage of the negotiations. When the term 'religion' was subsequently encountered more directly by Japanese translators, the formulation of new Japanese terms was required. For the Japanese in the 1850s, 'religion' was a diplomatic category, and no single word in Japanese could capture the contours of this Euro-American category. It was not until the 1870s that the generic concept of religion was popularised in Japan. This article examines the ways in which the Japanese elite engaged with the generic term 'religion' before the Japanese equivalent was developed. It focuses on Japanese interactions with the discourse on 'religion' conveyed by Commodore Perry's expedition to Japan (1852-1854) and by Townsend Harris (1804-1878) who represented the United States in the subsequent negotiations. This resulted in the signing of the American- Japanese treaty in 1858, which guaranteed 'religious freedom' for American citizens in Japan. This article also highlights the American projection of 'religion' upon Japan. The articulation of 'religion' as a generic category, essentially distinct from the 'secular' realms of state', 'politics', 'economy', and the like, first appeared in the late seventeenth century. American narratives on 'religion' in the nineteenth century appear to be closely related to the norms and imperatives of imperialism. This article assesses the validity of such a claim in the context of the American-Japanese negotiations between 1853 and 1858. (English)